A supramolecular approach for the facile solubilization and separation of covalently functionalized single-walled carbon nanotubes - Bosch, Sebastian; Zeininger, Lukas; Hauke, Frank; Hirsch, Andreas; Hauke, Frank (Chemistry - A European Journal, 2014)
Through a combination of an electronic-type selective diazonium-based attachment of a Hamilton receptor unit onto the carbon nanotube framework and a supramolecular recognition approach of a cyanuric acid derivative, we herein introduce a highly promising strategy for the tuning of carbon nanotube solubility and, directly related to that, a solution-based easy and straightforward separation of covalently functionalized carbon nanotube derivatives with respect to their unfunctionalized counterparts. The supramolecular complexation of the cyanuric acid derivative provides the driving force for the dramatically increased dispersibility and for the long-time stability of the individualized single-walled carbon nanotube derivatives in chloroform. The selective covalent functionalization of metallic carbon nanotubes can easily be analyzed with the aid of scanning Raman microscopy techniques. The functional derivatives have furthermore been characterized by UV/Vis-NIR and fluorescence spectroscopy as well as by mass spectrometric coupled thermogravimetric analysis. The investigation of the supramolecular complexation is based on an in-depth UV/Vis-NIR analysis and atomic force microscopy investigations. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Density gradient ultracentrifugation on carbon nanotubes according to structural integrity as a foundation for an absolute purity evaluation - Backes, Claudia; Bosch, Sebastian; Mundloch, Udo; Hauke, Frank; Hirsch, Andreas; Hauke, Frank (ChemPhysChem, 2011)
Ultrapure: The absolute purity of defect-free and structurally perfect single-walled carbon nanotubes in a bulk sample can be determined with density gradient ultracentrifugation (see picture). The experimental protocol offers a quick and reliable tool and is applicable to a broad variety of nanotube materials to evaluation production and purification procedures. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

New basic insight into reductive functionalization sequences of single walled carbon nanotubes (SWCNTs) - Hof, Ferdinand; Bosch, Sebastian; Eigler, Siegfried; Hauke, Frank; Hirsch, Andreas (Journal of the American Chemical Society, 2013)
The reactivity of reduced single walled carbon nanotubes (SWCNTs) (carbon nanotubides), prepared under strict inert conditions in a glovebox with respect to the covalent functionalization with hexyl iodide and subsequent exposure to ambient conditions (air, moisture), was systematically investigated by Raman, absorption, fluorescence, and IR spectroscopy as well as by TG/MS measurements. We have discovered that the alkylation does not lead to a complete discharging of the tubes since follow-up reactions with moisture still take place leading to mixed functionalized carbon nanotube derivatives containing H- and OH-addends (but no carboxylates) next to the hexyl groups. This was confirmed by the exposure of carbon nanotubides to ambient conditions. The degree of hexylation determined both under strict inert (ic) and ambient (ac) conditions increases with an increasing K:C ratio of the reduced SWCNT starting material. The presence of OH-groups covalently attached to the nanotubes was also confirmed by postfunctionalization reactions with 2-thiophenecarbonyl chloride, leading to the corresponding esters. Control experiments with KO give rise to the formation of the same oxygen functionalities. These combined findings allowed for the suggestions of a plausible reaction mechanism, describing all the observed reactions on the SWCNTs side walls. The amount of subsequent side reactions after the treatment of reduced SWCNTs with electrophiles is strongly influenced by the reduction potential of the electrophile, which is responsible for the extent of reoxidation. Incomplete quenching of negative charges allows stronger oxidants/electrophile (e.g., O) to perform follow-up reactions. © 2013 American Chemical Societ

Selective reduction of SWCNTs-concepts and insights - Gebhardt, Julian; Bosch, Sebastian; Hof, Ferdinand; Hauke, Frank; Hirsch, Andreas; Görling, Andreas (Journal of Materials Chemistry C, 2017)

Statistical raman spectroscopy: An method for the characterization of covalently functionalized single-walled carbon nanotubes - Hof, Ferdinand; Bosch, Sebastian; Englert, Jan; Hirsch, Andreas; Hauke, Frank (Angewandte Chemie International Edition, 2012)
Dedicated to Professor François Diederich on the occasion of his 60th birthday A powerful method based on statistical Raman analysis has been developed for the classification of the degree of functionalization, electronic selectivity, and sample homogeneity of functionalized carbon nanotubes (CNTs). The outcome of addition reactions to CNTs can easily be analyzed and quantitated by the determination of three characteristic Raman indices: the Raman defect (RDI), homogeneity (RHI), and selectivity index (RSI). Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.